THE LANGUAGE OF TRADERSÃ¢â¬â¢ COMMUNITY IN KLEWER TRADITIONAL MARKET SALA: A SOCIOLINGUISTICS ROLE IN PRESERVING TRADITION - Utami, Triyoga Dharma (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2009)
This paper aims to describe the realization of language use, recognize the verbal interaction patterns in trading and socializing and identify the determinants of language use by the Javanese community with their non-Javanese speech-partners. The study refers to the sociolinguistic theory, based on the qualitative research by the author in 2004. Supporting data collected is daily conversation at the research location. It is found that the language use by the kiosk-owners and their workers as the members of Javanese tradersÃ¢â¬â¢ community is closely related to their everyday social relations. The language used is Bahasa Indonesia, Javanese language and mixture of the both. The determinant factors of language use are divided into lingual and non-lingual factors. The lingual factors include Sala dialect, speech level, and Javanese language position as a mother tongue. The non-lingual factors include the multiculturalism relating to the speakerÃ¢â¬â¢s diversity of their ethnic backgrounds, realization of social relationships among the speakers, and cultural traditions. Key word: language use, sociolinguistics, cultural traditions, the city of Sala